Effects of raising area and pasture type on carcass and meat characteristics of barbarine lambs - Smeti S.; Mekki I.; Azizi C.; Yagoubi Y.; Mahouachi M.; Atti N. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
The aim of this study was to characterize the lamb meat of the mountainous areas of the Northwest “Djebel” of Tunisia. Lambs of Djebel group (D) were reared in a region characterized by mountainous terrain and soil unsuitable for crops, lambs grazed natural forests with dominance of woody species. While in the region of Bou-Rebiaa (BR) and Oueslatia (O), grazing pasture is based on herbaceous and lambs were supplemented with concentrate and hay. At the age of 6 months, lambs (12 from Djebel; 12 from Bou-Rebiaa and 11 lambs from Oueslatia area) were slaughtered. Lambs’ slaughter body weight (SBW) was affected by the pasture type (25.8, 26.8 and 22.6 kg for Djebel, Bou-Rebiaa and Oueslatia region, respectively). Also, higher carcass weight and higher dressing percentage were recorded for lambs from Djebel and Bou-Rebiaa. Similarly, the skin, head and feet weights were higher for these groups; these organs are strongly correlated to the SBW which was higher for Djebel and Bou-Rebiaa regions. Similarly, higher ultimate pH and lower meat lightness (L*) were recorded for lambs from Djebel area. In conclusion, lambs grazing natural forests in the mountainous area presented similar carcass weight and SBW to those supplemented with hay and concentrate. Investigations on meat composition and eating quality are needed to characterize Djebel meat.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)